Cash Flow Risk Management Practices on Sustainable Financial Performance in Sri Lanka - Wickramasinghe., M.B.; Gunawardane, K. (My University, 2017)
Recent year’s global economic crisis have urged the businesses all over the world to committed cash flow risk management practices and sharing information with environment, social and economic actives transparency for stockholders. This research aims to explore the impact of risk management practises and how they have applied toaccomplish sustainable financial performance in Sri Lanka and offer guidance to all the businesses as to how they can mitigate the risk faced by them.The research has expanded to extensive coverage of business sectors by 65 listed companies and secondary data were obtained from the annual reports publication in CSE. The statistical analysis of the multiple regression technique performed to calculate the results using e view-9 software. Risk management practices in operating cash flow have negative correlation between sustainable financial performances. The study was revealed that investment cash flow risk management practices have no correlation between sustainable financial performances. This will give detailed idea of cash flow risk management practises involvements and the importance to the listed companies in Sri Lanka. Keywords: Risk management practices, operating, financial, investment, shareholder’s equity, cash flow, sustainable financial performance